High turnover photocatalytic hydrogen formation with an Fe(iii) N-heterocyclic carbene photosensitiser. Issue 35 (4th April 2022) - Schwarz, Jesper; Ilic, Aleksandra; Johnson, Catherine; Lomoth, Reiner; Wärnmark, Kenneth
Abstract : The first high turnover photocatalytic hydrogen formation reaction using an earth-abundant iron photosensitiser is presented. Abstract : Herein we report the first high turnover photocatalytic hydrogen formation reaction based on an earth-abundant Fe III -NHC photosensitiser. The reaction occurs via reductive quenching of the 2 LMCT excited state that can be directly excited with green light and employs either Pt-colloids or [Co(dmgH)2 pyCl] as proton reduction catalysts and [HNEt3 ][BF4 ] and triethanolamine/triethylamine as proton and electron donors. The outstanding photostability of the Fe III -NHC complex enables turnover numbers >1000 without degradation.